A New Coupled Approach for Enthalpy Pumping Consideration in a Free Piston Stirling Engine (FPSE) - Majidniya, Mahdi; Mabrouk, Mohamed Tahar; Kheiri, Abdelhamid; Remy, Benjamin; Boileau, Thierry (Applied Mechanics, 2022)
One group of losses that can considerably affect the performance of Free Piston Stirling Engines’ (FPSE) is the enthalpy pumping and the shuttle effect, which are due to the gap standing between the cylinder and the displacer. The shuttle effect is induced by the periodic displacer motion between the hot and the cold sources. The enthalpy pumping, which is the subject of the present study, is due to the short-circuit-like flow between the hot and cold spaces. To study these losses, first, a fine nonlinear dynamic model of the FPSE is developed and validated. Then, to study the enthalpy pumping based on that, a coupled model (for the first time) and a decoupled model are presented. The difference between the two models is that the first one provides a dynamic and a thermic linkage between the Stirling and loss model, while the second one studies them separately. The effect of the gap size on both loss models was investigated. The coupled and decoupled modeling results were quite different due to the considerable effect of the enthalpy pumping on the FPSE response. The results showed that the enthalpy pumping in the decoupled model exceeds the total output power when the gap exceeds 30 μm, and when the gap exceeds 70 μm, the enthalpy pumping is around ten times larger than the output power. In contrast, the enthalpy pumping in the coupled model is always less than the output power, which is logical. Thus, the coupled one was presented as the adapted model that should be considered for further FPSE studies.